Vegetation Characteristics of Fallow Plots and Soil Erosion in South-Western Nigeria - Oke, S. O.; Isichei, A. O.; Aina, P. O. (2014)
A study was carried out to find out the magnitude of runoff and sediment yield and various vegetation parameters .in Ile-Ife area of south western Nigeria. Seven 50 x 50 111 sample plots in Ile-Ife area, Nigeria were selected; one plot in a relatively undisturbed secondary forest and six other plots in disturbed areas with ages ranging from one year to five years old. Results showed that plots in younger fallows had fewer woody species and individuals than the older plot. A comparison of the bare and vegetated plots clearly sided that development of vegetation affects physical and chemical soil characteristics. The bare plot produced the highest values of both runoff sediment yield followed distantly by the natural forest plot while the disturbed young plots with lesser tree densities had the lowest runoff and sediment yield.